TOKOH DAN PENAFSIR BERPENGARUH DALAM KARYA TAFSIR MUHAMMAD ABDUH - Tamrin Tamrin (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2010)
Abstract: Muhammad Abduh is a influencing figure in religious field in the end of 19th and 20th century. He offered constructive ideas, especially in tafsîr field. The ideas is valued by some Muslim intelectual only as connecting from previously figure. Some influencing figures in Abduh’s tafsîr are Syaykh Darwisyi in Sufisme, Sayyid Jamâl al-Dîn al-Afghânî in Logic, Jurnalism, and Science. He also interested in Imâm al-Ghazâli’s essays, al-Zamakhsyâri’s Tafsîr al-Kasysyâf, Jalâl al-Dîn al-Suyūtī’s and Jalâl al-Dīn al-Mahallī’s Tafsîr Jalâlayn, Fakhr al-Râzi’s Tafsîr mafâtih al-Ghayb, al-Nasafī’s Madârik al-Tanzîl wa Haqâiq al-Ta'wîl, and al-Baydhâwi’s Anwâr al-Tanzîl wa Asrâr al-Ta'wîl. Key Words: Tafsîr, Abduh, al-Ghazâli, al-Nasafī, al-Baydhâwi, al-Zamakhsyâri, al-Thabari, dan Fakhr al-Râzi